PENGARUH LINGKUNGAN KERJA, STRES KERJA, DAN DISIPLIN KERJA TERHADAP PERILAKU CYBERLOAFING PADA PEGAWAI DINAS PENDIDIKAN KABUPATEN BANYUMAS - Niken Kharisma Pambayun; Hengky Widhiandono; Akhmad Darmawan; Alfalisyado Alfalisyado (Universitas Bina Taruna Gorontalo, 2024)
The research conducted by the researchers aimed to analyze the influence of the work environment, work stress, and work discipline on cyberloafing behavior in employees of the Banyumas Regency Education Service. This research is quantitative. The variables of work environment, work stress, and work discipline are independent, while cyberloafing behavior is the dependent variable. The respondents were 87 employees, with a census sampling technique so that the population and research sample were all respondents. Statistical analysis uses SmartPLS 3.0 as a research analysis tool to test validity, reliability, and hypotheses. The research results show that the work environment has a negative and significant influence on cyberloafing behavior, work stress has a positive and significant influence on cyberloafing behavior, and work discipline has a negative and insignificant influence on cyberloafing behavior. In conclusion, special attention is needed to work stress by superiors to reduce the possibility of employee doing cyberloafing behavior.